PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF PADA MATA PELAJARAN GEOGRAFI - Sahat Siagian; Lingin lingin (Jurnal Teknologi Pendidikan (JTP), 2012)
This research is aimed to : (1) develop a good interactive Instructional media, easy to be learnt, and can be used for individual learning, (2) examine the effectiveness of theinteractive instructional media in Geography. This study is developmental research uses Borg & Gall’s model combined with Dick & Carey’s. The development of this instructional product is systematically proceeded in six steps; research and information collecting, planning, developing preliminary product, validating, trying out, revising, and producing final product. The subjects of preliminary field testing are two experts in Geography, two experts in instructional design,two experts in media product, three students for one-to-one try out, nine students for small group try out, and fifty one students for large group try out. The instruments employed in this study is a questionnaire and analyzed by using descriptive statistics. The findings of the study conclude that the quality of the developed instructional is excellent. The final product ofthis interactive instructional media is continued with effectiveness test. The study takes place in SMA Sutomo 1 Medan to the students of X class, academic year 2011-2012. The method used in this study is quasi experiment. The samples are 96 students consisting 50 students as experiment class given interactive Instructional media while the others given text book as control class. The result of hypothesis test proof that the study results of the students taught show a significant difference between using interactive instructional media and the text book. (Fcount = 5.19 > Ftable = 1.95). The effectiveness of the interactive instructional media is 82.55%higher than the text book 71.84%.